Biogenic production of silver nanoparticles by Enterobacter cloacae Ism26 - EL-BAGHDADY, Khaled Z. (Turk J Biol, 2018)
A bacterial isolate capable of tolerating 30 mM silver nitrate (AgNO3) was recovered from soil contaminated with industrial waste. The isolate was identified by 16S rRNA as Enterobacter cloacae Ism26 (KP988024) and its capability to synthesize silver nanoparticles (AgNPs) was investigated. AgNPs were produced by mixing 1 mM AgNO3 solution with bacterial cell lysate under light conditions. The UV-Vis spectrum of the aqueous medium containing AgNPs exhibited a peak at 440 nm corresponding to the surface plasmon resonance of the AgNPs. The crystalline nature of the particles was confirmed by X-ray difractometer. High-resolution transmission electron microscopy revealed that the AgNPs were spherical and well dispersed and ranged in size from 7 to 25 nm. The average size range of the produced AgNPs was confirmed by dynamic light scattering. Fourier transform infrared spectroscopy revealed possible involvement of reductive groups on the surface of the nanoparticles. The biosynthesized AgNPs were stable for 6 months and inhibited both gram-positive and gram-negative bacteria. This work describes the exploitation of a low-cost biomaterial and an easy method for the synthesis of AgNPs with desirable and advantageous characteristics.